Recent Advances of the NLRP3 Inflammasome in Central Nervous System Disorders - Keren Zhou; Ligen Shi; Yan Wang; Sheng Chen; Jianmin Zhang (Journal of Immunology Research)
Inflammasomes are multiprotein complexes that trigger the activation of caspases-1 and subsequently the maturation of proinflammatory cytokines interleukin-1β and interleukin-18. These cytokines play a critical role in mediating inflammation and innate immunity response. Among various inflammasome complexes, the NLRP3 inflammasome is the best characterized, which has been demonstrated as a crucial role in various diseases. Here, we review recently described mechanisms that are involved in the activation and regulation of NLRP3 inflammasome. In addition, we summarize the recent researches on the role of NLRP3 inflammasome in central nervous system (CNS) diseases, including traumatic brain injury, ischemic stroke and hemorrhagic stroke, brain tumor, neurodegenerative diseases, and other CNS diseases. In conclusion, the NLRP3 inflammasome may be a promising therapeutic target for these CNS diseases.